Procedural Results and Early Clinical out Come after PTCA in Elderly Patients - Rawat, B; Bhatta, Y; Pandey, A; Pandey, M; Poudyal, P; Verma, P; Agrawal, P; Kasliwal, RR (Nepalese Heart Journal, 2004)
The study was undertaken to obtain data regarding the procedural results and early clinical out come of the elderly patients who underwent PTCA for symptomatic CAD, Out of 63 patients who underwent PTCA, 17 (26.98%) were elderly patients of age above 65 years. The study group consisted of 11 (64.70%) male and 6 (35.29%) female patients. The majority of the patients, 13 (76.47%) had associated HTN.